PENGARUH PENERAPAN METODE GAME EDUKASI TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM MATERI AKU ANAK SALEH KELAS V DI SEKOLAH SDN 7 PALELEH KABUPATEN BUOL - Dewi Nursafitri S. Hasani (Educativa: Jurnal Pendidikan Agama Islam, 2024)
This study aims to determine the effect of implementing educational games on students’ learning outcomes in Islamic Religious Education (IRE) subjects for fifth-grade students at SDN 07 Paleleh, Buol Regency. The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group model. The subjects consisted of two classes: an experimental class that received treatment through educational games and a control class that used conventional teaching methods. Data collection was conducted through learning outcome tests administered in the form of pretests and posttests. The data were analyzed using prerequisite tests (normality and homogeneity tests), paired sample t-tests, and effectiveness analysis using the normalized gain (N-Gain) method. The results revealed a significant improvement in learning outcomes in the experimental class. The average posttest score in the experimental class was 81.33, higher than the control class average of 62.00. The paired sample t-test showed a significance value of 0.000 (p < 0.05), indicating a significant effect of the educational game method on learning outcomes. Furthermore, the N-Gain score of the experimental class was 57.75%, categorized as “moderately effective,” while the control class scored only 20.28%, categorized as “ineffective.” These findings suggest that the educational game method is an effective instructional strategy for improving student learning outcomes in Islamic Religious Education at the elementary school level.